2015
DOI: 10.1007/s10393-015-1038-z
|View full text |Cite
|
Sign up to set email alerts
|

Daily Movements and Microhabitat Selection of Hantavirus Reservoirs and Other Sigmodontinae Rodent Species that Inhabit a Protected Natural Area of Argentina

Abstract: Abundance, distribution, movement patterns, and habitat selection of a reservoir species influence the dispersal of zoonotic pathogens, and hence, the risk for humans. Movements and microhabitat use of rodent species, and their potential role in the transmission of hantavirus were studied in Otamendi Natural Reserve, Buenos Aires, Argentina. Movement estimators and qualitative characteristics of rodent paths were determined by means of a spool and line device method. Sampling was conducted during November and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…The wide range of heights used was not only passages but provided places to live in that we found nests at two metres above the ground. These results reinforce the pattern detected with a smaller sample size in Maroli, Vadell, Iglesias, Padula, and Gómez Villafañe (). Udrizar‐Sauthier, Abba, and Udrizar‐Sauthier () also found Oligoryzomys sp.…”
Section: Discussionsupporting
confidence: 88%
“…The wide range of heights used was not only passages but provided places to live in that we found nests at two metres above the ground. These results reinforce the pattern detected with a smaller sample size in Maroli, Vadell, Iglesias, Padula, and Gómez Villafañe (). Udrizar‐Sauthier, Abba, and Udrizar‐Sauthier () also found Oligoryzomys sp.…”
Section: Discussionsupporting
confidence: 88%
“…and O. rufus were aggregated most of the time. Closeness between these two species has been also described in other habitats (Maroli et al 2015) and may provide opportunities for the horizontal transmission of hantavirus among species, leading to spillover and host-switching events. For instance, an individual of O. rufus has recently been found infected with Pergamino hantavirus (Colombo et al 2019), a genotype which had been so far associated with A. azarae exclusively.…”
Section: Discussionmentioning
confidence: 93%
“…Antibodies in the D. kempi Kemp grass mouse were probably caused by a spillover event ( 2 ). Maroli et al ( 9 ) demonstrated that A. azarae grass mice share regions with other rodents, suggesting that these mice could promote spillover infections. Antibody prevalence in A. azarae grass mice was 23.9%, which exceeded prevalences reported in other areas of the Argentinean pampas ( 10 ).…”
Section: The Studymentioning
confidence: 99%
“…In addition, male A. azarae grass mice (estimate 1.4440; p = 0.0027) ( Table 1 ) were more frequently infected than female mice, probably because of aggressive encounters with other rodents ( 1 ). Maroli et al ( 9 ) reported that longer A. azarae grass mice travel greater distances, increasing the probability of intraspecific encounters and potential hantavirus transmission.…”
Section: The Studymentioning
confidence: 99%